Dampak Pengembangan Sumber Daya Manusia terhadap Kinerja Pegawai Kantor DISDUKCAPIL Kabupaten Pangkajene dan Kepulauan - Muh. Alam Nasyrah Hanafi; Hadi, Abdurrahman; Burhami, Abdul Hafid; Ulfa, Maria (Yayasan Literasi Sains Indonesia, 2025)
This research is a quantitative research with the aim of determining the impact of human resource development on employee performance at the Population and Civil Registration Office of Pangkajene and Kepulauan Regency. The variables used are human resource development and employee performance using a data collection method by distributing questionnaires to 86 employees who were used as research samples. The collection technique used saturated sampling. The data analysis methods used in this study were validity tests, reliability tests, simple linear regression analysis, correlation coefficient tests, determination coefficient tests, and t-tests. The results of this study indicate that human resource development and employee performance have a significant impact on employee performance. The Population and Civil Registration Office of Pangkajene and Kepulauan Regency is expected to improve employee performance based on the results of research that has been conducted showing that the indicator